HSMA: An O(N) electrostatics package implemented in LAMMPS - Liang, Jiuyang; Yuan, Jiaxing; Xu, Zhenli (Computer physics communications, 2022)
We implement two recently developed fast Coulomb solvers, HSMA3D (Zhao et al. (2018) [49]) and HSMA2D (Liang et al. (2020) [50]), into a new user package HSMA for the molecular dynamics simulation engine LAMMPS. The HSMA package is designed for efficient and accurate modeling of electrostatic interactions in 3D and 2D periodic systems with dielectric effects at O(N) cost. The implementation is hybrid MPI and OpenMP parallelized and compatible with existing LAMMPS functionalities. The vectorization technique following AVX512 instructions is adopted for acceleration. To establish the validity of our implementation, we have presented extensive comparisons to the widely used particle-particle particle-mesh (PPPM) algorithm in LAMMPS and other dielectric solvers. With the proper choice of algorithm parameters and parallelization setup, the package enables calculations of electrostatic interactions that is efficient especially for systems with dielectric mismatch. Program Title: HSMA CPC Library link to program files:https://doi.org/10.17632/z39zyh573s.1 Developer's repository link:https://github.com/LiangJiuyang/HSMA-Harmonic-surface-mapping-algorithm-in-LAMMPS Licensing provisions: GPLv3 Programming language: C++ Nature of problem: Evaluation of long-range electrostatic interactions for charged system with fully periodic condition or confined by planar dielectric interfaces. Solution method: We implement the Harmonic Surface Mapping algorithm (HSMA), which combines the image-charge method with the harmonic surface mapping and converts the contribution of infinite images into a finite number of surface charges on an auxiliary sphere, into simulation package LAMMPS. The HSMA package works for both fully periodic systems and partially periodic systems with planar dielectric interfaces, achieving truly linear O(N) complexity by employing fast multipole method. Our package can be applied to general all-atom simulations and a broad range of charged complex fluids under dielectric confinement. Additional comments including restrictions and unusual features: Hybrid MPI plus OpenMP parallelization is used in HSMA package for high-performance computing. We provide vector optimization by using the AVX512 instructions and Intel MKL library for further acceleration. The Intel Parallel Studio is required for these techniques.